COMMUNICATION PATTERNS OF DEAF STUDENTS WITH HEARING LECTURER IN THE CLASSROOM (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Deaf people communicate differently, such as using sign language or writing. This communication style difference becomes a problem when a deaf person is in higher education, where most of the communication is verbal orally. Most deaf students in the university in Indonesia do not have a standardized facility to help them study in class; therefore, each student could have a different communication style during class lectures. This article identifies the classroom communication patterns between deaf students and hearing lecturers. The research's informants are deaf students from three universities in Central Java. The characteristics of the informant are; 1) deaf student, 2) use more than one communication medium, and 3) the communication with the teacher happened in the classroom (offline class). This study uses a qualitative approach with a phenomenological method to understand the phenomenon of deaf students in the classroom—data obtained through in-depth interviews and literature study. The results of this study indicate that deaf students have a variety of communication styles in classrooms, such as a mobile application called Live Transcribe, a note taker, and an interpreter. However, there are still many obstacles, such as the transcripts from the application that are not per the speech, note takers that do not give a piece of comprehensive information, and the limited number of interpreters. Therefore, the students must change the media communication regularly depending on the situation to overcome those problems. To cite this article (7th APA style): Aprilia, R. & Nisa, F. K. (2022). Communication patterns of deaf students with hearing lecturer in the classroom. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 135-145. https://doi.org/10.36782/jcs.v12i2.2277